Swift heavy ions induced controlled biodegradation of poly(ε-caprolactone) nanohybrids - Tiwari V.K.; Singh N.K.; Avasthi D.K.; Misra M.; Maiti P. (My University, 2025)
Swift heavy ions (SHI) induced modification of biodegradable poly(ε-caprolactone) (PCL) nanohybrids (NH) with organically modified nanoclay has been studied for structural, thermal, surface morphology and sol-gel analyses and its function to control biodegradation. Nanohybrids retain its structure and thermal stability even at higher irradiation fluence. Surface morphology of nanohybrid indicates insignificant changes in roughness after irradiation at high fluence vis-à-vis marked degradation in pristine PCL. Sol-gel analyses suggest that crosslinking is a major phenomenon in nanohybrid in presence of nanoclay against chain session in pure PCL. These induced properties in PCL/nanohybrid caused by SHI irradiation affect the biodegradation in a pure enzymatic medium. Before irradiation, nanohybrids show greater biodegradation as compared to pure PCL, whereas it exhibits less degradation after irradiation due to extensive crosslinked network in nanohybrid in presence of nanoclay raising SHI induced controlled biodegradation in polymer. Morphological studies confirm the regulated biodegradation after irradiation in pure PCL and its nanohybrids. © 2012 Elsevier Ltd.